Cell therapy to improve regeneration of skeletal muscle injuries. Issue 3 (6th March 2019) - Qazi, Taimoor H.; Duda, Georg N.; Ort, Melanie J.; Perka, Carsten; Geissler, Sven; Winkler, Tobias
Abstract: Diseases that jeopardize the musculoskeletal system and cause chronic impairment are prevalent throughout the Western world. In Germany alone, ~1.8 million patients suffer from these diseases annually, and medical expenses have been reported to reach 34.2bn Euros. Although musculoskeletal disorders are seldom fatal, they compromise quality of life and diminish functional capacity. For example, musculoskeletal disorders incur an annual loss of over 0.8 million workforce years to the German economy. Among these diseases, traumatic skeletal muscle injuries are especially problematic because they can occur owing to a variety of causes and are very challenging to treat. In contrast to chronic muscle diseases such as dystrophy, sarcopenia, or cachexia, traumatic muscle injuries inflict damage to localized muscle groups. Although minor muscle trauma heals without severe consequences, no reliable clinical strategy exists to prevent excessive fibrosis or fatty degeneration, both of which occur after severe traumatic injury and contribute to muscle degeneration and dysfunction. Of the many proposed strategies, cell‐based approaches have shown the most promising results in numerous pre‐clinical studies and have demonstrated success in the handful of clinical trials performed so far. A number of myogenic and non‐myogenic cell types benefit muscle healing, either by directly participating in new tissue formation or by stimulating the endogenous processes of muscle repair. These cell types operate via distinct modes of action, and they demonstrate varying levels of feasibility for muscle regeneration depending, to an extent, on the muscle injury model used. While in some models the injury naturally resolves over time, other models have been developed to recapitulate the peculiarities of real‐life injuries and therefore mimic the structural and functional impairment observed in humans. Existing limitations of cell therapy approaches include issues related to autologous harvesting, expansion and sorting protocols, optimal dosage, and viability after transplantation. Several clinical trials have been performed to treat skeletal muscle injuries using myogenic progenitor cells or multipotent stromal cells, with promising outcomes. Recent improvements in our understanding of cell behaviour and the mechanistic basis for their modes of action have led to a new paradigm in cell therapies where physical, chemical, and signalling cues presented through biomaterials can instruct cells and enhance their regenerative capacity. Altogether, these studies and experiences provide a positive outlook on future opportunities towards innovative cell‐based solutions for treating traumatic muscle injuries—a so far unmet clinical need.